Arabian Humorous Story in The Book of NawÄdir JuhÄ Li Al-AtfÄl: A Linguistic Analysis - Asyifa Ulam; Emzir Emzir; Nuruddin Nuruddin (Jurnal Penelitian, 2018)
The purpose of this study is to describe (1) The compliances and deviationsof the principle of cooperation in the speech of Arabian humorous story â€œNawÄdir JuhÄ Li Al-AtfÄlâ€, (2) The speech context that happened in that story. This research uses descriptive methods with qualitative approach. The focus of this study is the speech ofcompliances and deviations of cooperation principle which is used in Arabian humorous story by uses methods and techniques to collect the data. In the provision of engineering log data is also used, namely selecting the text and record data that contain speech of compliance and deviation toward the principles of cooperation. The result of this research are the speech of Arabian humorous story â€œNawÄdir JuhÄ Li Al-AtfÄlâ€ contain elements of compliance and deviation toward the principles of cooperation which is all of four maxims, are: maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner.